TAFSIR AKADEMIK KARYA MAHMUD YUNUS: CORAK ILMIAH, SOSIAL DAN INTELEKTUAL DALAM TAFSIR AL-QUR’AN AL-KARIM - Nurus Syarifah (The Department of the Qur'anic Studies, Faculty of Ushuluddin, Adab, and Da'wah, State Institute of Islamic Studies (IAIN) Langsa, 2020)
This article describes the academic aspects of the interpretation of Mahmud Yunus which is named Tafsir Al-Qur’an al-Karim. This interpretation is one of the pioneers of Indonesian-language interpretation works that are widely used by the majority of Muslims in Indonesia. He dared to introduce the use of Latin letters for translation and interpretation of the Qur'an. The method used in this research is descriptive method. The conclusion of this study is that the academic aspects of Mahmud Yunus' interpretation work include scientific, social and intellectual styles. The scientific style in its interpretation is a new style that is associated with developing science, so its interpretation seems to emphasize the close relationship between the Qur'an and the development of science and technology which are the main characteristics of modern thought. The social and intellectual patterns are more demonstrated by Mahmud Yunus through the use of elements of common expressions, as well as traditions, customs and socio-cultural phenomena in their interpretation.